Alternaria Brassicae Induces Systemic Jasmonate Responses in Arabidopsis Which Travel to Neighboring Plants via a Piriformsopora Indica Hyphal Network and Activate Abscisic Acid Responses - Vahabi, Khabat; Reichelt, Michael; Scholz, Sandra S.; Furch, Alexandra C. U.; Matsuo, Mitsuhiro; Johnson, Joy M.; Sherameti, Irena; Gershenzon, Jonathan; Oelmüller, Ralf (Frontiers in Plant Science, 2018)
Stress information received by a particular local plant tissue is transferred to other tissues and neighboring plants, but how the information travels is not well understood. Application of Alternaria brassicae spores to Arabidopsis leaves or roots stimulates local accumulation of jasmonic acid (JA), the expression of JA-responsive genes, as well as of NITRATE TRANS-PORTER (NRT)2.5 and REDOX RESPONSIVE TRANSCRIPTION FACTOR1 (RRTF1). In-fection information is systemically spread over the entire seedling and propagates radially from infected to non-infected leaves, axially from leaves to roots, and vice versa. The local and systemic NRT2.5 responses are reduced in the jar 1 mutant, and the RRTF1 response in the rbohD mutant. Information about A. brassicae infection travels slowly to uninfected neighboring plants via a Piriformospora indica hyphal network, where NRT2.5 and RRTF1 are upregulated. The systemic A. brassicae-induced JA response in infected plants is converted to an abscisic acid (ABA) response in the neighboring plant where ABA and ABA-responsive genes are induced. We propose that the local threat information induced by A. brassicae infec-tion is spread over the entire plant and transferred to neighboring plants via a P. indica hyphal network. The JA-specific response is converted to a general ABA-mediated stress response in the neighboring plant.